2021
DOI: 10.1007/s13132-021-00837-3
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in Innovative Efforts: a Systematic Literature Review

Abstract: The importance of cooperation in innovation has been widely studied. Cooperative settings are potential platforms for the indirect and direct transmission of knowledge. This article aims to present the results of a systematic literature review on innovation cooperation. It covers topics such as the effects of cooperation according to different governance structures, cooperation drivers, partner's attributes, firm size, regional factors, and the host country's current stage of economic development. In general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…This goes in line with some earlier literature on the importance of government subsidies for cooperation for innovation (Abramovsky et al, 2009; Busom & Fernández‐Ribas, 2008; Franzò et al, 2023; Schwartz et al, 2012). We argue that these programs are built in many cases on partnerships that require companies to look for other companies or institutions with complementary sets of competences to develop a specific project, as suggested by Freire and Gonçalves (2022). The results show that companies that receive public financing from the EU are five times more likely to cooperate than companies that do not receive such funds.…”
Section: Discussionmentioning
confidence: 99%
“…This goes in line with some earlier literature on the importance of government subsidies for cooperation for innovation (Abramovsky et al, 2009; Busom & Fernández‐Ribas, 2008; Franzò et al, 2023; Schwartz et al, 2012). We argue that these programs are built in many cases on partnerships that require companies to look for other companies or institutions with complementary sets of competences to develop a specific project, as suggested by Freire and Gonçalves (2022). The results show that companies that receive public financing from the EU are five times more likely to cooperate than companies that do not receive such funds.…”
Section: Discussionmentioning
confidence: 99%
“…These spillovers can be a result of various interactions, such as collaboration, communication, networking, or even competition. According to a review of the literature, rms that value external information are more likely to engage in cooperation (Freire & Gonçalves, 2022). In the questionnaire, rms rated the importance of available information for their innovation activities from the following sources.…”
Section: Methodsmentioning
confidence: 99%
“…Firms that engage in cooperation for innovation are more likely than others to be innovative, and even to perform better and grow faster (Archibugi et Paunov, 2012). Beyond its importance at the microeconomic level, cooperative innovation also contributes towards the development of the National Innovation System (NIS) and may be a tool of industrial policy (Liu et al, 2017;Freire & Gonçalves, 2022). International cooperation 2 is often crucial for rms located in countries that are not at the forefront of science and technology since it enables them to access resources, knowledge, markets, and opportunities that may not be readily available within their own borders (Freire & Gonçalves, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, a large amount of research has already indicated that mutual trust may improve the collaborative relationship and help participating organizations generate intensive knowledge interaction (Alaaraj et al, 2018;Le and Lei, 2018). Participating organizations that have high trust in the cooperation projects may be more likely to accept collective decisions (Freire and Gonc ¸alves, 2021). Thus, trusted knowledge interaction may motivate participating teams to accept resources of other participating teams rather than adopt an adversarial position.…”
Section: Mediating Role Of Knowledge Interactionmentioning
confidence: 99%